Legal Protection against Legal Uncertainty of Tacit Approval under the Indonesian Job Creation Law - Bimasakti, Muhammad Adiguna (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2024)
The concept of tacit approval underscores the idea of considering an application or request as approved even without an explicit formal decision. This approach is taken when the government fails to address or respond to the application within a stipulated timeframe. In such cases, the absence of a response is interpreted as an implied granting of permission or approval. This can be found in article 175 point 7 of the Law No. 6 of 2023 concerning Enactment of Government Regulation in lieu of Law No. 2 of 2022 Concerning Job Creation as Law (Job Creation Law). However, this tacit approval must be further regulated through presidential regulation, yet up until this day, it has not been regulated. When the applicant can utilize tacit approval is uncertain, as well as uncertainty regarding legal recourse for the disadvantaged party concerning tacit approval. This research finds that the regulation of tacit approval in presidential regulation should involve acknowledging the tacit approval through registration within the government's information system and issuance of tacit approval certificate, thus ensuring legal certainty for the applicants of decisions. Subsequently, the registered tacit approval certificate can be reviewed through administrative court to establish legal certainty for affected citizen.